A Qualitative Investigation of Airborne Algae in Government Science College Campus Bengaluru, India - C., Sathish; Rekha, C.R.; C., Sahana; S., Shruthi (International Journal of Scientific Research in Biological Sciences, 2020)
Airborne algae are one of the bio components of the atmosphere. They are the least studied organisms in aerobiology although they may exert an unfavourable impact on human health. Airborne algae remain viable in the atmosphere in the form of spores and filaments. To study the diversity of airborne algae in the Government Science College campus, Bangalore, the experiments were conducted by selecting four sites. Air samples were collected by the Petri plate exposure method using Benecks agar medium. A total of fifteen airborne algae belonging to twelve genera were identified and recorded. They belong to the class Cyanophyceae, Chlorophyceae, and Bacillariophyceae. Cyanophycean members were the dominant airborne algae over Chlorophyceae and Bacillariophyceae, with a total of seven genera. These were Oscillatoria, Lyngbya, Microcoleus, Chroococcus, Nostoc, Anabaena, Hapalosiphon, Gloeocapsa, and Myxosarcina. The Bacillariophycean members were Cymbella and Nitzschia and Chlorophyceae was represented by Chlorella. The present studies on airborne algae have shown that the majority of species present in air samples were soil algae.